Vertical Flow Assays: Vertical Flow Assay for Inflammatory Biomarkers Based on Nanofluidic Channel Array and SERS Nanotags (Small 32/2020). Issue 32 (13th August 2020) - Chen, Ruipeng; Du, Xin; Cui, Yujun; Zhang, Xieyuan; Ge, Qinyu; Dong, Jian; Zhao, Xiangwei
Abstract : For multiplex and ultrasensitive quantification of inflammatory biomarkers in point‐of‐care testing (POCT) scenarios, Xiangwei Zhao and co‐workers introduce anodic aluminum oxide (AAO) with an ordered nanofluidic channel array into vertical flow assays in combination with SERS nanotags in article number 2002801, which results in amplified signals, improved immunoreaction kinetics and detection repeatability.